2022
DOI: 10.1186/s12888-022-04006-x
|View full text |Cite
|
Sign up to set email alerts
|

Do interventions principally targeting excessive alcohol use in young people improve depression symptoms?: a systematic review and meta-analysis

Abstract: Background Excessive alcohol use is common in young people and is associated with a range of adverse consequences including an increased risk of depression. Alcohol interventions are known to be effective in young people, however it is not known if these interventions can also improve depression. Objective To investigate whether psychosocial interventions principally targeting excessive alcohol use in young people reduce depression symptoms compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Our finding of significant reductions in depression and psychological distress, following an intervention aimed narrowly at reducing alcohol consumption, are congruent with the results of previous longitudinal studies showing that reductions in alcohol consumption led to reductions in depressive symptoms [ 12 , 18 ]. Crucially, our data demonstrate that changes in levels of alcohol consumption are associated with reductions in depressive symptoms, supporting the hypothesis that problem drinking precipitates and/or maintains depression and psychological distress [ 14 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our finding of significant reductions in depression and psychological distress, following an intervention aimed narrowly at reducing alcohol consumption, are congruent with the results of previous longitudinal studies showing that reductions in alcohol consumption led to reductions in depressive symptoms [ 12 , 18 ]. Crucially, our data demonstrate that changes in levels of alcohol consumption are associated with reductions in depressive symptoms, supporting the hypothesis that problem drinking precipitates and/or maintains depression and psychological distress [ 14 ].…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, convincing evidence shows that the course of harmful alcohol use can be effectively altered by brief interventions, which can be feasibly implemented in primary health care settings [ 15 17 ]. One systematic review and meta-analysis found that interventions targeting excessive alcohol use in young people resulted in a significant reduction in depression symptoms [ 18 ], but it is unclear if this is also the case among PWH. Our study aimed to establish whether a brief intervention focused on reducing alcohol consumption among PWH who met criteria for hazardous alcohol use but not dependence has any significant effect on symptoms of depression among patients on antiretroviral therapy in Tshwane, SA.…”
Section: Introductionmentioning
confidence: 99%
“…Underweight and sarcopenia are also risk factors for depression 26,27 . Excessive alcohol consumption is a risk factor for depression 28 . Consumption of ultra‐processed foods (processed foods high in sugar, salt, and fat, produced by industrial processes using additives such as hydrogenated oils, added sugars, flavors, emulsifiers, and preservatives) is associated with depression and depressive symptoms 29 .…”
Section: Rehabilitation Nutrition For Depressionmentioning
confidence: 99%
“… 26 , 27 Excessive alcohol consumption is a risk factor for depression. 28 Consumption of ultra‐processed foods (processed foods high in sugar, salt, and fat, produced by industrial processes using additives such as hydrogenated oils, added sugars, flavors, emulsifiers, and preservatives) is associated with depression and depressive symptoms. 29 In adolescents, consumption of junk food (foods high in energy, salt, and fat, with an imbalance of nutrients) is associated with depression, stress, anxiety, and sleep dissatisfaction.…”
Section: Rehabilitation Nutrition For Depressionmentioning
confidence: 99%